Skeleton in the closet: hidden diversity in patterns of cranial and postcranial ontogeny in Neotropical direct-developing frogs (Anura: Brachycephaloidea) - Vera Candioti, Florencia (2020)
Direct development implies transformations with respect to the anuran biphasic life cycle, including changes in embryonic anatomy. In the clade Brachycephaloidea, skeletal ontogeny is known inEleutherodactylus coquiof the basal family Eleutherodactylidae. In this work, we study it in four species representing the two other families in the group. We worked with developmental series ofOreobates barituensis,Haddadus binotatus,Ischnocnema henselii, andBrachycephalus ephippium. Specimens were prepared following protocols of clearing and staining and histology. In the cranium, results show an overall shared pattern that, as summarized forE. coqui, combines a partial recapitulation of aspects of the ancestral biphasic ontogeny with a profound remodeling that includes lost/novel structures and heterochronic shifts of developmental events. Among these transformations are the absence of suprarostrals and trabecular horns and the precocious ossification of jaw and suspensorium. In addition, each lineage shows particular features such that skull ontogeny varies interspecifically. In turn, the morphogenesis of the axial and appendicular skeleton is highly conserved, with main variations including the extent of ossification at hatching. Along with some external features such as the egg tooth and the enveloping tail with transversely arranged fins, an ossification sequence with extremely accelerated ossification of jaws and suspensorium could be distinctive of Brachycephaloidea.